HIV and risk behaviors of persons of low socio-economic status, Popayan-Colombia (2008-2009) (Colombia Medica, 2013)
Objective: To determine HIV presence and risk behaviors of persons of low socio-economic status in the city of Popayan, Colombia.Methods: Cross-sectional study; between 2008 and 2009, 363 participants of Popayan signed informed consent and received pre and post HIV test counseling. Socio-demographic characteristics and history of STDs, risk behaviors and previous HIV testing were assessed. Descriptive statistics, correlations and multivariate logistic regression were calculated.Results: Mean age 33.5±10.2; 66.0% women. Frequency of HIV positive patients was 3.86% (95% CI: 1.87-5.85), greater in men (7.38%; p= 0.013). Greater frequency of HIV-positive patients was observed in people age 29-37, those without a stable partner, and those with history of risky alcohol consumption (more than five drinks in 2 hrs).Conclusions: HIV-positive patients frequency in this population was greater than national estimate for general population, aged 15-49 in Colombia, with even greater frequency in men. This study suggests that characteristics associated with low socioeconomic status, in economically active population, without a stable partner and with risky alcohol use, can potentially increase risk of HIV infection